2016
DOI: 10.1111/jsap.12444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pancreatic, hepatic and renal microscopic lesions in post‐mortem samples from cavalier King Charles spaniels

Abstract: 24The Cavalier King Charles Spaniel is a common breed in the UK. Chronic valvular 25 disease and syringohydromyelia are frequently reported in this breed but there is less 26 information on other diseases despite a suspicion of over-representation. 28The goal of this study was to describe the prevalence of pancreatic, hepatic and renal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…47%) had a final diagnosis of a disease that could be related to the hepatobiliary system; of which, one of seven (14%) was a primary hepatic disease and two of seven (28%) had diseases that are known to cause secondary hepatic dysfunction, although neither case showed clinical evidence of hepatic disease. In a prevalence study, histopathological lesions of primary hepatic disease were reported in 11% of CKCS, which showed no ante mortem signs of hepatic disease (Kent et al 2016), which is similar to the 12% prevalence of chronic hepatitis reported in the general population of dogs (Watson et al 2010) and the results found in this study. In our study, in other dog breeds, one of 10 (10%) showed evidence of primary hepatic involvement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…47%) had a final diagnosis of a disease that could be related to the hepatobiliary system; of which, one of seven (14%) was a primary hepatic disease and two of seven (28%) had diseases that are known to cause secondary hepatic dysfunction, although neither case showed clinical evidence of hepatic disease. In a prevalence study, histopathological lesions of primary hepatic disease were reported in 11% of CKCS, which showed no ante mortem signs of hepatic disease (Kent et al 2016), which is similar to the 12% prevalence of chronic hepatitis reported in the general population of dogs (Watson et al 2010) and the results found in this study. In our study, in other dog breeds, one of 10 (10%) showed evidence of primary hepatic involvement.…”
Section: Discussionsupporting
confidence: 90%
“…In a prevalence study, histopathological lesions of primary hepatic disease were reported in 11% of CKCS, which showed no ante mortem signs of hepatic disease (Kent et al . ), which is similar to the 12% prevalence of chronic hepatitis reported in the general population of dogs (Watson et al . ) and the results found in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Cervicothoracic torticollis is thought to be due to asymmetrical damage of the dorsal gray column, over a number of spinal cord segments, resulting in an imbalance of afferent proprioceptive information from the cervical neuromuscular spindles. 17,43 Comorbidities were common and not unexpected given the breed disposition to MVD, 44 pancreatic disorders, 45 keratoconjunctivitis sicca, 46 and other neurological disorders. 6,21 Other than ascertaining that a group was not predisposed to a certain comorbidities, detailed analysis was not preformed because of the retrospective and likely incomplete nature of the study, for example, MVD was the most common comorbidity present in approximately 1 in 5 CKCS but cannot be translated as the lifetime risk of a CM-/SM-affected dog having MVD because this disease is more common in older CKCS.…”
Section: Comorbiditiesmentioning
confidence: 99%
“… 1 , 6 However, some necropsy‐based studies do not distinguish between different histopathologic forms of CP, and do not correlate histologic abnormalities with clinical findings. 1 , 7 , 8 , 9 , 10 Consequently, the clinical importance of postmortem findings of pancreatic inflammation and fibrosis are mostly unknown. 1 , 7 , 8 , 9 , 10 Obtaining pancreatic biopsies antemortem is invasive.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 7 , 8 , 9 , 10 Consequently, the clinical importance of postmortem findings of pancreatic inflammation and fibrosis are mostly unknown. 1 , 7 , 8 , 9 , 10 Obtaining pancreatic biopsies antemortem is invasive. Moreover, biopsies might be diagnostically insensitive to detect mild or early CP, because of patchy lesion distribution and limited tissue sample size.…”
Section: Introductionmentioning
confidence: 99%